Afro-Brazilian Heritage in the Context of Quilombola School Education - Elaine Monteiro; Maria Clareth Gonçalves Reis (Universidade Federal do Rio Grande do Sul, 2019)
This article proposes reflections on quilombola childhoods, in the plural. It starts with the conception of quilombo to discuss values that base relations of care and education of childhood and affirm the black identity. Childhoods in quilombola communities in the state of Rio de Janeiro, field of action and research of the authors, and changes in the insertion of children in Jongo as affirmation of quilombola identity are presented as contribution to the proposed reflections. Finally, based on legal frameworks in the field of education and questioning challenges posed to the implementation of the National Curriculum Guidelines for Quilombola School Education, it discusses quilombolaeducation as a duty and right of memory and affirmation of black identity.